Computer simulations of water-mediated force between phospholipid membranes - Pertsin, Alexander; Grunze, Michael (Current opinion in colloid & interface science, 2011)
The knowledge of forces operating between phospholipid bilayer membranes in water and aqueous solutions is a prerequisite for understanding membrane-membrane coupling phenomena such as stacking, adhesion, and fusion. This explains the substantial efforts undertaken in the last two decades to measure and rationalize the intermembrane force as a function of separation, with an emphasis on short-range repulsion. Despite considerable progress in experimental measurements, the interpretation of the force-distance curves in terms of physically distinct force components involves serious difficulties because the experiment provides only the total magnitude of the force. All this imparts importance to computer simulations, that allow direct evaluation of the intermembrane force and its components through the respective ensemble averages. In this paper we briefly review these computer simulations, as well as some relevant studies. The simulation results are discussed in the context of the existing theories of the intermembrane forces.